Interdisciplinarity of Information Science and its contributions in the study of government data sharing on the internet - Moreira, Fabio Mosso [UNESP]; Pomim Valentim, Marta Ligia [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2018)
The internet can be considered an important alternative to enable greater interaction between public administration and society, and one of the actions refers to the sharing of governmental databases. This information flow involves specific questions that are studied in Information Science, which presents an interdisciplinary characteristic due to the complexity of its object, the use of theories and methodologies from other areas and the diversity of its scientific body. The objective of this research was to identify the fields of knowledge that present an interdisciplinary interaction with Information Science, to highlight which of them can contribute to the study of the sharing of governmental data on the internet, and to relate disciplines of the area with the analysis of the aspects present in this informational flow. The Content Analysis method was applied, based on data collection at the official portals of the University of Sao Paulo, Ribeirao Preto campus, Federal University of Sao Carlos and Federal University of Santa Catarina, in order to identify the curricular structure of undergraduate courses with focus on the Information Science area in Brazil and analyze their teaching plans. The results indicate which areas of knowledge are interdisciplinary to Information Science and which ones can contribute to the study of the aspects involved in the process of sharing government data on the internet. In addition, it also highlights which disciplines make up the structure of undergraduate courses analyzed and that can effectively contribute to the study of this information flow.
Keywords: Interdisciplinary; Information science; Data sharing; Government data; Information flows